2019
DOI: 10.1177/2050157918822131
|View full text |Cite
|
Sign up to set email alerts
|

Selfies in the wild: Studying selfie photography as a local practice

Abstract: Previous research on selfies has primarily focused on selfies as media products rather than as an activity. In this paper, we examine selfies as a situated practice, connecting the social media phenomenon to the local spaces where it is performed. Based on ethnographic studies of selfie photography, we present and discuss three aspects of selfies in the wild. First, we consider selfies as part of a larger photographic context and show how they are often taken in series with other genres of images. Second, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 35 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Through observation, we found that one of the important motives of individual selfie behavior is life logging, and at the same time, this kind of selfie image that expresses oneself in a given way focuses on performance or ideal self-expression, which enables the youth group to realize the mental world or emotional world in the virtual network space under the pressure of realistic anxiety and life pressure to achieve self-revelation, and present the self-expression with the help of media technology. Everyone has the right to record their life and show themselves, and the act of selfie image publishing and photo editing reflects the individual’s creative life more, making information dissemination more diversified and autonomous ( Weilenmann and Hillman, 2020 ). Individuals’ image shaping in social media is graspable, and selfie photos become the key to individuals’ self-shaping as well as forming good impression management, reflecting a higher degree of motivation in online interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Through observation, we found that one of the important motives of individual selfie behavior is life logging, and at the same time, this kind of selfie image that expresses oneself in a given way focuses on performance or ideal self-expression, which enables the youth group to realize the mental world or emotional world in the virtual network space under the pressure of realistic anxiety and life pressure to achieve self-revelation, and present the self-expression with the help of media technology. Everyone has the right to record their life and show themselves, and the act of selfie image publishing and photo editing reflects the individual’s creative life more, making information dissemination more diversified and autonomous ( Weilenmann and Hillman, 2020 ). Individuals’ image shaping in social media is graspable, and selfie photos become the key to individuals’ self-shaping as well as forming good impression management, reflecting a higher degree of motivation in online interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The context of the photo can provide more social cues to the viewer by helping visualize information that the body and face cannot present. The presentation of profile photos is a kind of situated practice (Weilenmann & Hillman, 2020), and contextual cues play an essential role in gay men's visual socialization. This study provided a new important dimension for exploring the effects of social cues in CMC.…”
Section: The Ambiance Effect Of Background Scenes In Self-presentationmentioning
confidence: 99%
“…Others have a strong focus on one particular type of photo tourists take, such as food (Wachyuni and Yusuf, 2021; Wong et al, 2019), or ‘selfies’ (Christou et al, 2020; Dinhopl and Gretzel, 2016; Taylor, 2020). Weilenmann and Hillman (2020) found that while selfies are important, tourists also take photos of other aspects of their tourism experience, such as animals and scenery. This present study specifically asked research participants about their photo-taking motivation and content.…”
Section: Literature Reviewmentioning
confidence: 99%